Psychiatric Nurse Reports on the Quality of Psychiatric Care in General Hospitals - Hanrahan, Nancy P. (2008)
Although acute inpatient psychiatric care has changed dramatically over the past 2 decades, little is known about how these changes have affected the quality of care, psychiatric nurse staffing, or patient outcomes. The purpose of this report is to explore the quality of care, quality of the practice environment, and adverse events as assessed by psychiatric nurses in the general hospital setting. The study sample consisted of 456 registered nurses permanently assigned to psychiatric units, compared with a larger sample of 11 071 registered nurses who work permanently on medical, surgical, or medical-surgical units. Compared with nonpsychiatric nurses, psychiatric nurse characteristics reveal an older, more experienced workforce, with a higher proportion of male nurses. Nurses rated quality of patient care lower in the psychiatric specialty than in the medical-surgical specialty. Furthermore, psychiatric nurses reported significant concern about the readiness of patients for discharge and higher incidence of adverse events. They also experienced more verbal abuse, physical injuries, and complaints from patients and families. Collectively, the results from this study underscore the organizational problems and quality-of-care issues that cause psychiatric nurses in general hospital settings to evaluate their work environments negatively.